Monocytes and macrophages in malignant melanoma. II. Lysis of antibody-coated human erythrocytes as an assay of monocyte function. - Nyholm, R. E. (Nature Publishing Group, 1978)
Peripheral blood mononuclear cells will lyse antibody-treated human erythrocytes. Using Group A red cells and a hyperimmune anti-A1 serum, we have devised a microassay for the cytolytic capacity of mononuclear cell suspensions. The effector cells responsible for red-cell lysis are mononuclear, adherent and phagocytic, and their activity is blocked by aggregated IgG. Their presence correlates well with non-specific esterase-containing cells and we conclude that they are monocytes. Dose-response curves of red-cell lysis plotted against numbers of monocytes were used to derive a simple parameter expressing the number of monocytes needed to lyse 15% of the 51Cr-labelled red cells. The assay was applied to a group of 27 normal controls and 36 patients with a histologically proven diagnosis of malignant melanoma. The results indicate that monocytes from patients show significantly greater lytic activity than those from the controls. These data suggest that monocytes from cancer patients are in some way activated, and that other defects in monocyte function which have been detected in cancer patients (defective chemotaxis and maturation) may be associated with monocyte "activation".